The Egerton gospel (Egerton papyrus 2 + Papyrus Köln VI 255) : introduction, critical edition, and commentary - Zelyck, Lorne R., 1978- (Texts and editions for New Testament study, 2019)
"In this commentary on the Egerton Gospel, Lorne R. Zelyck presents a fresh paleographical analysis and thorough reconstruction of the fragmentary text, which results in new readings and interpretations. Details surrounding the acquisition of the manuscript are presented for the first time, and various scholarly viewpoints on controversial topics, such as the date of composition and relationship to the canonical gospels, are addressed. This early apocryphal gospel (150-250 CE) provides traditional interpretations of the canonical gospels that are similar to those of other early Christian authors, and affirms Jesus' continuity with the miracle-working prophets Moses and Elisha, his obedience to the Law, divinity, and violent rejection by Jewish opponents"--